A novel molecular diagnostics platform for somatic and germline precision oncology. Issue 4 (23rd April 2017) - Cabanillas, Rubén; Diñeiro, Marta; Castillo, David; Pruneda, Patricia C.; Penas, Cristina; Cifuentes, Guadalupe A.; de Vicente, Álvaro; Durán, Noelia S.; Álvarez, Rebeca; Ordóñez, Gonzalo R.; Cadiñanos, Juan
Abstract: Background: Next‐generation sequencing (NGS) opens new options in clinical oncology, from therapy selection to genetic counseling. However, realization of this potential not only requires succeeding in the bioinformatics and interpretation of the results, but also in their integration into the clinical practice. We have developed a novel NGS diagnostic platform aimed at detecting (1) somatic genomic alterations associated with the response to approved targeted cancer therapies and (2) germline mutations predisposing to hereditary malignancies. Methods: Next‐generation sequencing libraries enriched in the exons of 215 cancer genes (97 for therapy selection and 148 for predisposition, with 30 informative for both applications), as well as selected introns from 17 genes involved in drug‐related rearrangements, were prepared from 39 tumors (paraffin‐embedded tissues/cytologies), 36 germline samples (blood) and 10 cell lines using hybrid capture. Analysis of NGS results was performed with specifically developed bioinformatics pipelines. Results: The platform detects single‐nucleotide variants (SNVs) and insertions/deletions (indels) with sensitivity and specificity >99.5% (allelic frequency ≥0.1), as well as copy‐number variants (CNVs) and rearrangements. Somatic testing identified tailored approved targeted drugs in 35/39 tumors (89.74%), showing a diagnostic yield comparable to that of leading commercial platforms. A somatic EGFR p.E746_S752delinsA mutation in a mediastinal metastasis from a breast cancer prompted its anatomopathologic reassessment, its definite reclassification as a lung cancer and its treatment with gefitinib (partial response sustained for 15 months). Testing of 36 germline samples identified two pathogenic mutations (in CDKN2A and BRCA2 ). We propose a strategy for interpretation and reporting of results adaptable to the aim of the request, the availability of tumor and/or normal samples and the scope of the informed consent. Conclusion: With an adequate methodology, it is possible to translate to the clinical practice the latest advances in precision oncology, integrating under the same platform the identification of somatic and germline genomic alterations. Abstract : This work describes the development, validation and clinical application of a novel molecular diagnostics platform based on targeted NGS, specifically designed to comprehensively identify, in a single test, both (1) somatic alterations linked to sensitivity or resistance to approved cancer therapies and (2) germline mutations predisposing to familial cancer. We also propose an innovative framework for analysis, interpretation and reporting of results, which adapts to different combinatorial situations regarding the nature of the request, the availability of tumor/normal samples and the scope of the informed consent. The analytical sensitivity and specificity of the platform for detecting SNVs and indels are >99.5% and its application to patient samples identified targeted therapeutic opportunities, revealed one case of misdiagnosis and detected germline pathogenic mutations.